Are South African Socially Responsible Investment Funds Doing Well While Doing Good? - Peerbhai, Faeezah; Naidoo, Jeremy (Acta Universitatis Danubius. Œconomica, 2022)
In recent years, the popularity of socially responsible investment (SRI) funds has soared as individuals are driven towards more environmentally and socially conscious investments. However, SRI funds could incur substantial costs whilst trying to comply with the principles of environmental, social and corporate governance (ESG). The question of financial performance is vital for investors who go beyond philanthropic affinities. The objective of this study is therefore to evaluate the risk-adjusted performance of South African SRI funds relative to their conventional funds and respective passive benchmarks. To achieve this objective, the performance of 23 South African SRI funds is examined from January 2008 to December 2018 using the Fama and French 3-factor and Carhart 4-factor models. The results of this study indicate that SRI funds underperformed relative to non-SRI funds in earlier periods but outperformed or exhibited no significant performance difference in latter periods (or despite underperforming in both sub-periods, the SRI funds underperformed by a smaller margin in latter periods). This improved performance of SRI funds is attributed to the ‘learning effect’. The implications of this findings for South African investors are discussed further.